Hospital Prevalence of Colorectal Cancer among Colonoscopy Recipients Attending a Tertiary Hospital in Oman: A Cross-Sectional Study - Alanoud F. Alsumait; Yahya M. Al-Farsi; Mostafa I. Waly; Issa S. Al-Qarshoobi; Samir Al-Adawi; Nawaf H. Albali; Mansour S. Al-Moundhri (The Scientific World Journal)
Purpose. Evidence from industrialized/developed countries showed that colorectal cancer (CRC) incidence rates have significantly dropped due to the widespread use of colonoscopy. In Arab countries, however, the CRC had been reported to have increased. Despite the concerted effort in the primary prevention and widespread use of colonoscopy, to our knowledge, there have been no reports of the prevalence rate of CRC among colonoscopy recipients from Oman. This study aims to explore the CRC prevalence estimates over selected sociodemographic characteristics among colonoscopy-recipients at a tertiary hospital in Oman over five years of follow-up. The regional variations in Oman were also examined in this study. Methods. This hospital-based cross-sectional study reviewed reports of colonoscopies performed over 5-years of retrospective follow-up at a tertiary hospital in Oman. CRC prevalence estimates were calculated over age, gender, governorate, and time of follow-up. Results. A total of 442 CRC cases were enumerated among 3701 colonoscopies, with an overall CRC prevalence estimate of 11.9 per 100 colonoscopies (95% CI: 10.9, 13.0). Gender-specific CRC prevalence was higher among males compared with females (13.3 vs. 10.5). Age-specific CRC prevalence increased with advancing age, from 2.8 among those less than 40 years of age to 26.5 among aged 70 years or more. Regional CRC prevalence was highest among residents in Batinah Governorate. Over the 5-years of follow-up, there was a slow rise in CRC prevalence with an annual increment of 0.59%. Conclusion. The study provides supportive evidence for a steady increase in CRC prevalence over age categories and years of follow-up and depicted the variations of gender-specific CRC prevalence estimates over increasing age categories. The study calls for timely formulation and adoption of national CRC screening programs centered on the colonoscopy use as primary prevention and maximizing its utilization and efficiency.